Pemberdayaan Masyarakat Melalui Inovasi Kesehatan dan Lingkungan di Desa Sungai Kayu Ara Kabupaten Siak - Sakur, Sakur; Ramadani, M.Yahya; Nabila, Rahma; Zulhendri, Zulhendri; Hidayat, Adityawarman; Yusrina, Etika; Ediputra, Kasman (EL-EMIR INSTITUTE, 2025)
Community empowerment through innovation in the health and environmental sectors is a strategic step to improve the quality of life and community resilience to various health and environmental problems. The Universitas Riau and Universitas Pahlawan Tuanku Tambusai Service Team Work Program in Sungai Kayu Ara Village, Siak Regency, aims to educate and empower the community through three main activities, namely the socialization of Clean and Healthy Living Behavior (PHBS) at SDN 06 Sungai Kayu Ara, the socialization of making soap from eco enzyme, as well as socializing the manufacture of dishwashing soap and water purifier. This program is implemented with a community participation-based approach, aiming to reduce dependence on products made from dangerous chemicals and provide practical, environmentally friendly solutions. The first activity was carried out on 12 October 2024, followed by the second activity on 16 October 2024, and the third activity on 6 December 2024. The results of this activity showed an increase in public knowledge regarding PHBS and the use of natural ingredients in everyday life, which had a positive impact on a healthier and environmentally friendly lifestyle.